2005
DOI: 10.4049/jimmunol.174.5.2645
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Manipulation of Dendritic Cells Overcomes Tolerance to Unmodified Tumor-Associated Self Antigens and Induces Potent Antitumor Immunity

Abstract: Most tumor-associated Ags are self proteins that fail to elicit a T cell response as a consequence of immune tolerance. Dendritic cells (DCs) generated ex vivo have been used to break tolerance against such self Ags; however, in vitro manipulation of DCs is cumbersome and difficult to control, resulting in vaccines of variable potency. To address this problem we developed a method for loading and activating DCs, in situ, by first directing sufficient numbers of DCs to peripheral tissues using Flt3 ligand and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
35
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 47 publications
5
35
0
Order By: Relevance
“…Vaccination approaches that target endogenous self/tumor-reactive T CD8 have met with varying levels of success in a number of tumor models (34,(42)(43)(44)(45)(46)(47)(48)(49). Unfortunately, such self-reactive cells are often subject to peripheral tolerance, limiting their effectiveness against progressing tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination approaches that target endogenous self/tumor-reactive T CD8 have met with varying levels of success in a number of tumor models (34,(42)(43)(44)(45)(46)(47)(48)(49). Unfortunately, such self-reactive cells are often subject to peripheral tolerance, limiting their effectiveness against progressing tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Mature DCs activated through TLR pattern recognition receptors produce proinflammatory cytokines, including IL-6, which can render responder T cells refractory to the suppressive effect of Treg (54). Independent studies have demonstrated that activation of APCs via innate immune receptors can break self tolerance (55), and that even in vivo manipulation of DCs (by CpG) can overcome tolerance to unmodified (tumor-associated) self-Ags and induces potent immunity (56). Once again a conflicting report concluded that DCspecific CD4 T cell help activation by TLR ligands was insufficient to break peripheral cross-tolerance (57).…”
Section: Discussionmentioning
confidence: 99%
“…48 Subversion of immunological tolerance toward leukemia might open novel therapeutic avenues to achieve successful anti-leukemia immunity. Strengthening the priming of antileukemia CD4 responses, for example, by forced expression of the tumor-necrosis factor LIGHT 49 or by optimized technologies allowing in vivo manipulation of DCs, 50 may eventually translate into clinically effective immunotherapeutic strategies to treat patients with leukemia.…”
Section: Discussionmentioning
confidence: 99%